PENGEMBANGAN SISTEM INFORMASI ABSENSI KARYAWAN PADA PT. META PROPERTI INDONESIA BERBASIS ANDROID MENGGUNAKAN PEMODELAN UML (UNIFIED MODELING LANGUAGE) - Doni Sitohang (Computer Technology and Information Systems, 2022)
PT. Meta Properti Indonesia is a medium-sized company engaged in primary and secondary propertyagency. This company has an employee attendance system that is still running manually. So that timeinefficiency in the attendance recording process becomes something that is always passed at the endof every month. With the above reasons, the author tries to provide an alternative by making anattendance system application that records data and employee attendance lists, arrival times and returntimes. Thus eliminating the process of recording employee attendance which has been runningmanually and also by using the attendance method using the company's Wifi where employees arerequired to be in the company will reduce the level of attendance input errors. This paper will alsoexplain the stages of work, starting from data collection, data analysis, planning and research schedulerelations to the implementation stage using UML (Unified Modeling Language) modeling. And makeuse case diagrams, sequence diagrams, class diagrams, flow maps and display input and output.